Exploring Strategies of Incorporating Multicultural Values in the Teaching and Learning Process at an Inclusive Primary School in North Bali - Ni Nyoman Padmadewi; Luh Putu Artini; Nengah Suparta; Putu Kerti Nitiasih; I Gede Wahyu Suwela Antara; Ni Made Yuniari (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2026)
Incorporating multicultural values into the process of teaching and learning in school is important for enhancing inclusivity. There has been an abundance of studies conducted on this topic; however, most of them were conducted on special related subject matters, and there are limited resources for exploring strategies of how multicultural values can be implemented in all dimensions of school life. This study aims to explore strategies for incorporating multicultural values in an inclusive school. The study was conducted in the form of a case study in a private full-inclusion primary school in North Bali, considered a favourite and successful school in implementing multicultural values by the society around the school. The teachers have received specialized trainings to support and teach autistic students in an inclusive class. The school has 12 students with mild autism spectrum disorder (ASD) integrated with neurotypical students in every grade from grades 1 to 6. The data were gathered over a period of six months through observations, in-depth interviews, and document analysis and were subsequently analysed qualitatively. This study found three main results. First, the school uses eight integrated strategies, five through activities that are part of the curriculum and three through activities that are not part of the curriculum. Second, these strategies have effects on many levels, such as more empathy, cooperation, less prejudice, more cultural pride, better critical thinking, and stronger social ties. Third, teachers' answers to the questionnaire show that they have consistently strong positive views about the program's cognitive, interpersonal, civic, and global outcomes. The study implied that the strategies positively influence students' attitudes and holistic development.